Studi Kasus Efektivitas Test IVA dan DNA HPV terhadap Deteksi Dini Kanker Serviks di Puskesmas Gayamsari - Reza Rahma Kumala; Rindang Kasih Parawansha Hariyoko; Qomariyah Qomariyah; Arina Nurmayasari (Natural: Jurnal Pelaksanaan Pengabdian Bergerak bersama Masyarakat., 2024)
Cervical cancer remains a major health problem with a high proportion of diagnoses in advanced stages. At the Gayamsari Community Health Center, IVA and HPV DNA tests are implemented as primary screening to prevent cervical cancer. This study aims to determine the effectiveness of the IVA test and HPV DNA in early detection of cervical cancer. The approach in this research is qualitative with a case study type. This subject selection was carried out on women who had previously had sexual relations and were vulnerable to HIV exposure at the Gayamsari Community Health Center. The methods used to collect data are observation, interviews and documentation.